Approach to cardiac arrest in adults (Portuguese Journal of Family Medicine and General Practice, 2010)
The Cardio-respiratory arrest is an infrequent situation in the Primary Care (PC) setting. However the family doctor and the other PC health units staff must be prepared to act in these situations. The advanced life support algorithm was defined in the European Resuscitation Council Guidelines, based on the scientific evidence available or in expert consensus. Its applicability in the PC setting is discussed in this article.
Keywords: Advanced Life Support; Cardiac Arrest; Primary Health Care